Rebranding and the evolving roles of information specialists in a knowledge society - Tokwe, H. (Midlands State University, 2016)
Rebranding has changed the way many institutions operate. Libraries, archive and record centres, museums, NGOs and Information Resource Centres are embracing rebranding of their services in response to the impact of the knowledge society. The knowledge society involves the use of networked information technologies, the Internet, and electronic resources such as e-journals, e-books and ecommerce. All these have transformed the information specialistís role. This paper is conceptual one and it considers rebranding in the context of the library. It goes further by clearly defining rebranding as it relates to the Information Specialists. The paper attempts to answer the question, who is the Information Specialist? The new evolving roles of the Information Specialists are described in greater detail. The paper concludes by finally bringing out the challenges that the Information Specialists face in a bid to deal with the challenges of the knowledge society.